Peningkatan Kinerja Melalui Orientasi Kewirausahaan, Kemampuan Manajemen, dan Strategi Bisnis (Studi pada Industri Kecil Menengah Bordir di Jawa Timur) (Jurnal Manajemen dan Kewirausahaan, 2009)
This research is conducted to investigate the influence of entrepreneurship orientation with emphasis on the management skills of the entrepreneur, and business strategy towards performance.the research is applied to the small and middle enterprise (sme) of embroidery industries in east java which have to encounter dynamic and uncertain environment and high intensity competition and need good management skills and appropriate business strategy in order to win in the competition. The population of the research is the entrepreneurs who are also the owners and managers of the small and middle embroidery industries in east java. The research used survey method and for that reason samples are needed. The sampling techniques needed two stages (it was a two stage technique). The total samples were 314 samples taken from 5 research areas. Meanwhile, the testing of the influence of management skills variable towards business strategy showed that the business strategy was influenced by the management skills of sme. Besides, the management skills influence performance, the higher the management skills of the entrepreneurs the higher their performance.